2016
DOI: 10.1038/srep26016
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the cold plasma-stimulated medium by regulating medium’s composition

Abstract: Over past several years, the cold plasma-stimulated medium (PSM) has shown its remarkable anti-cancer capacity in par with the direct cold plasma irradiation on cancer cells or tumor tissues. Independent of the cold plasma device, PSM has noticeable advantage of being a flexible platform in cancer treatment. Currently, the largest disadvantage of PSM is its degradation during the storage over a wide temperature range. So far, to stabilize PSM, it must be remained frozen at −80 °C. In this study, we first revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 37 publications
2
121
0
Order By: Relevance
“…H 2 O 2 is an anti-tumor factor that is typically generated in solutions by plasma treatment475760. To investigate whether H 2 O 2 generated in PAL is responsible for the observed anti-tumor effects, we measured the H 2 O 2 concentrations of these solutions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 O 2 is an anti-tumor factor that is typically generated in solutions by plasma treatment475760. To investigate whether H 2 O 2 generated in PAL is responsible for the observed anti-tumor effects, we measured the H 2 O 2 concentrations of these solutions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cold plasma affects biological targets not only directly but also indirectly through the medium, which has broadened the potential applications of non-thermal atmospheric pressure plasma in medicine41424344454647484950. We have demonstrated that plasma-irradiated medium, also called plasma-activated medium (PAM), has anti-tumor effects against glioblastoma5152, as well as ovarian5354, gastric55, pancreatic56, and lung cancer cells57.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up work identified methionine in addition to cysteine as medium-containing amino acids that scavenged plasma species most effectively. 67 …”
Section: App Applicationsmentioning
confidence: 99%
“…Another approach is PAM, which is broadly defined as medium or solution following exposure to plasma (Tanaka et al , 2014b(Tanaka et al , 2015a2016a). PAM selectively kills cancer cells and induces apoptosis, as demonstrated independently by researchers worldwide (Yan et al 2014;Mohades et al 2015;Judee et al 2016;Kumar et al 2016;Yan et al 2016).…”
Section: Indirect Treatmentmentioning
confidence: 99%